The Effect of Podcast Hosts on Youtube Channel Satisfaction - Yuniar Taruna; Partogi Bungaran; Myra Tania Wida; Artha Sejati Ananda (Universitas Mercu Buana, 2023)
This study aims to investigate the effect of podcast hosts on the satisfaction of YouTube channel viewers. Using a sample of 250 participants, data were collected through an online survey that measured the participants' perceptions of podcast hosts and their satisfaction with the YouTube channel. The results of the study showed a positive relationship between the perceived attractiveness and expertise of podcast hosts and viewers' satisfaction with the YouTube channel. Additionally, the study found that the quality of the podcast's content moderated the relationship between the perceived attractiveness of the host and satisfaction with the YouTube channel. The findings of this study provide insights into the importance of the host's role in enhancing viewer satisfaction with the YouTube channel, particularly in the context of podcast content. Further research is recommended to explore the effects of other host characteristics and their impact on viewer satisfaction.